THE INFLUENCE OF DIMENSION SAMPLE ANALYSIS ON UNIAXIAL COMPRESSIVE TEST USING NUMERIC MODEL BASED ON MOHR-COULOMB CRITERIA - Alifya Putri Kurniawan, Adisa
Geotechnical is the study about the behaviour of earth and soils. One of the mechanical properties that needed in the geotechnical planning is unconfined compressive strength that obtained from unconfined compressive test (UCS test). The UCS test is carried out using samples of intact rock created in certain length and diameter. John (1972) conducted research about the effect of the dimensions of the intact rock on the UCS value and concluded that the UCS value would decrease along with the increase of the ratio between length and diameter of the intact rock. In this research, numerical modelling of the UCS test will be carried out using software named FLAC2D based on Mohr-Coulomb criterion. Data that used is the secondary data based on Hoek and Brown (1997) research for very good quality intact rock. The diameter of the intact rock fixed at 50 mm with length that adjusted based on ratio needed. This research has the same output as prior research by John (1920), which along with the increase of the ratio between length and diameter intact rock, the UCS value would decrease. Vice versa, along with the decrease of ratio between length and diameter intact rock, the UCS value would increase.